The Effects of Safinamide Adjunct Therapy on Depression and Apathy in Patients With Parkinson's Disease: Post-hoc Analysis of a Japanese Phase 2/3 Study - Hattori, Nobutaka; Kogo, Yuki; Koebis, Michinori; Ishida, Takayuki; Suzuki, Ippei; Tsuboi, Yoshio; Nomoto, Masahiro (Frontiers in Neurology, 2022)
Background and Purpose: Neuropsychiatric symptoms in Parkinson’s disease (PD) have been shown to significantly affect quality of life. We investigated the impact of safinamide on depression and apathy when administered as an adjunct to levodopa in Japanese patients with PD. Methods: This was a post hoc analysis of data from a phase 2/3 clinical study of safinamide in Japanese patients with PD experiencing wearing-off (JapicCTI-153056; https://www.clinicaltrials.jp/cti-user/trial/ShowDirect.jsp?japicId=JapicCTI-153056). Patients received placebo, safinamide 50 mg, or safinamide 100 mg as an adjunct therapy. The endpoints for this analysis were changes from baseline to Week 24 in the Unified Parkinson’s Disease Rating Scale (UPDRS) Part I item 3 (depression) and item 4 (apathy) scores and the Parkinson’s Disease Questionnaire (PDQ-39) ‘emotional well-being’ domain score. Subgroup analyses investigated the relationship between neuropsychologic symptoms and improvements in motor fluctuation and assessed which patient populations might be expected to obtain neuropsychologic benefit from safinamide. Results: Compared with placebo, safinamide (both doses) significantly improved UPDRS Part I item 3 scores in the overall analysis population, and the 100-mg dose improved UPDRS Part I item 4 scores in the population with apathy at baseline. Changes in the PDQ-39 ‘emotional well-being’ score showed numerical, but not significant, dose-related improvements. Notable reductions in depression were associated with a change in daily ON-time ≥ 1 hour, pain during OFF-time at baseline, and female sex. Conclusions: The results from this post hoc analysis of the Japanese phase 2/3 study suggest that safinamide could bring benefits to patients with PD who have mild depression, pain during the OFF phase. In addition, safinamide might provide particular benefits for patients with PD who have mild apathy and female.